Development of Karcis-Delay "Daily Activities" as a Speech Education Media for Children with Speech Delay - Pramitasari, Afrinar; Setyarum, Ariesma; Dewanto, Aji Cokro (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
Karcis-delay is a speech education card media that can be used to improve the speaking skills of speech delayed children. The purpose of this research is to 1) describe the analysis of Delayed Activity Ticket (Karcis-Delay) needs, 2) describe the design of Delayed Activity Ticket (Karcis-Delay) media product, and 3) describe the validation results of experts on the development of Delayed Activity Ticket (Karcis-Delay) media as an alternative speech therapy for children with speech delay disorders. The type of research used is Research and Development (R&D). Data in this study were collected using observation methods, Focus Group Discussions (FGD), and interviews. The results of this study are as follows: (1) Delayed Activity Tickets (Karcis-Delay) are needed as speech education media for children with speech delay, (2) the design of Delayed Activity Tickets (Karcis-Delay) is created according to the analysis of content needs, focusing on daily activity cards and their causes, and (3) the expert validation conducted includes media expert validation, language expert validation, and child psychology expert validation. Based on the expert validation results, it can be concluded that Delayed Activity Tickets (Karcis-Delay) "Daily Activities" are feasible as speech education media for children with speech delay.